The Importance of Financial Management for Small Businesses - Susilawati, Made (Penelitian dan Pengembangan Ilmu, 2024)
This research investigates the impact of financial technology (Fintech) on financial management in small businesses in developing countries. Small businesses in the region often face difficulties in accessing efficient and affordable financial services, which can hinder their growth and stability. Fintech offers solutions such as digital payments, peer-to-peer lending, financial management tools, and crowdfunding, increasing the accessibility and efficiency of financial services. This study was conducted as a systematic literature review using databases such as Scopus, Web of Science, Google Scholar, and IEEE Xplore, in which 100 relevant articles were identified through the PRISMA method. The findings show that Fintech adoption can increase financial inclusion, improve risk management, and reduce operational costs for small businesses in developing countries. However, challenges such as complex regulations and limited technological infrastructure need to be overcome. The implications of this research emphasize the potential of Fintech to drive inclusive economic growth by empowering underserved small businesses. This research aims to provide insight for policy makers, Fintech providers, and small business owners to develop effective strategies by utilizing technology for sustainable economic development.